Are physiotherapists reliable proxies for the recognition of pain in individuals with cerebral palsy? A cross sectional study. Issue 2 (April 2015) - Riquelme, Inmaculada; Cifre, Ignacio; Montoya, Pedro
Abstract: Background: Pain is an important problem for individuals with cerebral palsy (CP). In addition to pain associated to the pathology, individuals with CP are often exposed to physiotherapy procedures which may cause or relieve pain. Objective: The major aim of this study was to compare pain ratings self-reported by individuals with cerebral palsy and ratings about pain in others provided by their physiotherapists. Method: Cross-sectional study. Children and young adults with cerebral palsy ( n  = 50) and their physiotherapists ( n  = 18) completed semi-structured interviews about clinical pain, as well as about procedural pain and pain relief elicited by standardized health procedures. Moreover, pain ratings were obtained during the application of hamstring stretching and passive joint mobilization. Results: Moderate-to-high agreement was observed between individuals with cerebral palsy and their physiotherapists on presence and intensity of pain, pain interference with physical activities and current and retrospective pain ratings elicited by physiotherapy procedures. By contrast, agreement regarding pain relief elicited by physiotherapy techniques was low. Conclusions: Our data suggest that although physiotherapists may be reliable proxies for the recognition of pain in individuals with cerebral palsy, further research should be done to improve the communication between health professionals and individuals with cerebral palsy around pain.